2015
DOI: 10.1371/journal.pone.0120708
|View full text |Cite
|
Sign up to set email alerts
|

Spermine Alleviates Drought Stress in White Clover with Different Resistance by Influencing Carbohydrate Metabolism and Dehydrins Synthesis

Abstract: The objective of this research was to analyse whether ameliorating drought stress through exogenously applied spermine (Spm) was related to carbohydrate metabolism, dehydrins accumulation and the transcription of genes encoding dehydrins in two white clovers (drought-susceptible cv. ‘Ladino’ and drought-resistant cv. ‘Haifa’) under controlled drying conditions for 10 days. The results show that the application of Spm effectively alleviates negative effects caused by drought stress in both cultivars. Exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 70 publications
(72 reference statements)
4
36
0
1
Order By: Relevance
“…It has been observed that abiotic stress can induce increases in endogenous PA content in various plant species, which is important for adaptation to drought stress (Kusano et al, 2008 ; Zhou and Yu, 2010 ; Hu et al, 2012 ). Elevated endogenous PA content through exogenously applied Spd or Spm led to enhancement in drought tolerance in Arabidopsis thaliana (Kusano et al, 2007 ), rice ( Oryza sativa ) (Farooq et al, 2009 ), and creeping bentgrass ( Agrostis stolonifera ) (Li et al, 2015 ). In the current study, our results showed that endogenous PA content increased significantly in detached clover leaves under water stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that abiotic stress can induce increases in endogenous PA content in various plant species, which is important for adaptation to drought stress (Kusano et al, 2008 ; Zhou and Yu, 2010 ; Hu et al, 2012 ). Elevated endogenous PA content through exogenously applied Spd or Spm led to enhancement in drought tolerance in Arabidopsis thaliana (Kusano et al, 2007 ), rice ( Oryza sativa ) (Farooq et al, 2009 ), and creeping bentgrass ( Agrostis stolonifera ) (Li et al, 2015 ). In the current study, our results showed that endogenous PA content increased significantly in detached clover leaves under water stress.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that exogenous plant growth regulators such as ABA, cytokinin, PAs, and proline can induce dehydrins accumulation or the expression of genes encoding dehydrins associated with the improvement of stress tolerance in various plants species including white clover [ 41 , 42 , 43 ]. The study of Li et al has found that Spm could significantly promote the accumulation of dehydrins in white clover under osmotic stress, thereby improving the drought tolerance of white clover [ 44 ]. In the current study, we found that exogenous GABA significantly increased the accumulation of dehydrins (65 kDa) and expression levels of four genes encoding dehydrins ( SK2, Y2K, Y2SK , and dehydrin b ) during seeds germination under salt stress, indicating GABA-regulated seeds germination and stress tolerance were closely related to dehydrins accumulation in white clover in response to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…SPM is involved in membrane stability and osmotic adjustment, both important processes during the desiccation phase of seeds (Li et al, 2015b). Furthermore, several studies found that the exogenous application of SPM increased drought tolerance by elevating the activity of antioxidant enzymes, such as SOD and CAT, which then resulted in a decrease in ROS activity (Shi et al, 2010;Li et al, 2015a), indicating the effective role of this PA against abiotic stress. These findings corroborate with the SPM contents found for G. gardneriana seeds (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%